Measuring parent satisfaction in youth mental health services. Issue 3 (6th April 2021) - O'Reilly, Aileen; Donnelly, Alanna; Rogers, Jennifer; Maloney, Olive; O'Brien, Gillian; Doyle, Elizabeth
Abstract : Purpose: Measuring parent satisfaction is regarded as essential but there is a paucity of research reporting on parental satisfaction with community youth mental health services. This study aims to examine parent satisfaction with Jigsaw – a primary care youth mental health service. Design/methodology/approach: A measure of parent satisfaction was developed and administered to parents in 12 Jigsaw services over a two-year period ( n = 510, age range: 28 to 70 years) when young people and parents were ending their engagement with these services. Findings: Overall, parents had high levels of satisfaction with Jigsaw and their level of satisfaction did not vary depending on the parent or young person's age and/or gender. Examination of qualitative feedback revealed three overarching themes relating to growth and change in young people, parents and their families; strengths of the service and; suggestions for future service development. Analysis of the psychometric properties of the measure provided evidence for a two-factor structure examining satisfaction with the intervention and outcomes and service accessibility and facilities. Originality/value: This study represents one of the first efforts to measure parent satisfaction with primary care youth mental health services. It has resulted in the development of a brief measure that can be more widely administered to parents engaging with primary care youth mental health services.